SOSIALISASI APE (ALAT PERAGA EDUKATIF) UNTUK MENINGKATKAN KESIAPSIAGAAN BENCANA DI SDN 05 BADES, KECAMATAN PASIRIAN, KABUPATEN LUMAJANG - Lely Marthalina, Melda; Putri Amelia, Amanda; Tunjung Putih, Indira; Ali Akbar, Luthfi; Rizhqulloh, Moh; Lutfhi Charismanda, Muhammad; Arif Wahyudin, Muhammah; Putri Rizki Hapsari, Salsabila (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2022)
Bades Village, Pasirian District, Lumajang Regency is a village whose area is located between two active mountains, namely Mount Semeru and Mount Lamongan and a coastline that stretches from west to east so that there is the potential for extreme waves and tsunamis. The geographical location of Bades Village causes the potential for several natural disaster threats such as tsunamis, landslides, and earthquakes. Therefore, disaster mitigation education is needed from an early age, especially for elementary school students. Disaster mitigation education can be done in several ways, one of which is using Educational Props (APE). The purpose of this devotion is to raise awareness and respond to the arrival of unpredictable disasters. So that these students are expected to have knowledge of pre-disaster mitigation and in times of disaster and can share their knowledge with the community. In addition, the method used in this socialization activity gives a new color in its delivery to elementary school students. The method used is the observation method, then held a socialization with the students of SDN 05 Bades, Kecamtan Pasirian, Lumajang Regency. The subjects of socialization were 40 elementary school students in grades 4 –6. The result of this service and research is an increase in knowledge of mitigating natural disasters that occur. Students are enthusiastic and interested in this socialization so that they are able to apply the material that has been given when the disaster comes.